How do Andalusian NGDOs Address Sexual and Female Reproductive Rights? Centrality, Approaches and Located Practices - Hernández-Ascanio, José; de la Mata-Agudo, Maria del Carmen (Revista de Estudios Andaluces, 2020)
Currently we see that the approach to female sexual and reproductive rights in the field of development cooperation is experiencing a double tension: on the one hand, cooperation agents, especially Non-Governmental Development Organizations (NGDOs) have prioritized their attention over this theme, in the measure in which efforts have been redoubled to prevent, reduce and eradicate the effects of gender inequalities in different areas. On the other hand, there is a clear setback in the exercise and enjoyment of these types of rights worldwide. A possible explanatory hypothesis for this tension is that the different ways of conceptualizing female Sexual and Reproductive Rights condition the situated practices of organizations insofar as they significantly affect their reason for being and their organizational nature. That is why the objective of this work is to investigate how female sexual and reproductive rights are configured and condition the reason for being, the nature and the situated practice of NGDOs. For this, a case study is carried out, the object of which was the development cooperation system in Andalusia. A combination of quantitative - qualitative methodologies was used, although in this work we are going to prioritize the results derived from the structural and dialectical techniques as they are especially significant. This work shows that Andalusian NGDOs move between a tension marked by a proactive interest in this type of rights and a structural deficit of competences to be able to manage them effectively.